2015
DOI: 10.1016/j.fertnstert.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study into the value of the automated Elecsys antimüllerian hormone assay for the assessment of the ovarian growing follicle pool

Abstract: The novel fully automated Elecsys AMH assay shows good correlations with age and AFC in women of reproductive age, providing a reproducible measure of the growing follicle pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…A strong correlation between FNPO and AMH has been established in infertile patients and in the general population (7,18,19,21). Despite the rather small sample size in our study, we also found a strong correlation between FNPO and serum AMH levels, both in the group of hormonal contraceptive users and in nonusers.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A strong correlation between FNPO and AMH has been established in infertile patients and in the general population (7,18,19,21). Despite the rather small sample size in our study, we also found a strong correlation between FNPO and serum AMH levels, both in the group of hormonal contraceptive users and in nonusers.…”
Section: Discussionsupporting
confidence: 61%
“…Assessment of female reproductive hormone levels typically includes serum analysis of the reproductive pituitary hormones FSH and LH, the ovarian hormone E 2 , and the adrenal hormone DHEAS. Ovarian reserve testing commonly involves a pelvic ultrasound scan to assess antral follicle count (AFC) and analysis of circulating serum antim€ ullerian hormone (AMH), which has emerged as a reliable marker for ovarian reserve, given its strong correlation with AFC (7).…”
mentioning
confidence: 99%
“…Clinical performance of AMH for prediction of hyper-responders was defined in two ways: classification accuracy was assessed by receiver operating characteristic (ROC) analyses and the corresponding area under the curve (AUC) [21], and clinical performance was evaluated by applying a pre-specified cut-off of 15.0 pmol/L (2.10 ng/mL) [16,17]. Sensitivity for detecting hyper-response; specificity for detecting non-hyper-response (poor and/ or normal response), poor response and normal response; positive predictive values; and negative predictive values were also calculated.…”
Section: Sample Measurement and Statistical Analysismentioning
confidence: 99%
“…The new, fully automated AMH assays, which allow for more efficient sample processing, should help to further reduce the influence of procedural errors (Iliodromiti et al, 2014a), and preliminary evidence suggests consistent AMH values are obtained under most storage conditions (Gassner and Jung, 2014). A recent study evaluating the fully automated Elecsys AMH assay from Roche reported consistent AMH values that were correlated with age and AFC across different centres (Anderson et al, 2015). Of note, significant variation in AFC was seen, suggesting that AMH level measured with the Elecsys assay may be a better indicator of ovarian reserve than AFC.…”
Section: Advantages and Disadvantages Of Amh Levelmentioning
confidence: 99%